Standing long jump performance is enhanced when using an external as well as holistic focus of attention: a kinematic study - Saemi, E.; Hasanvand, A.; Doustan, M.; Asadi, A.; Becker, K. (Sensors, 2024)
Standing long jump is known as one of the important skills in the success of athletes in most sports. In addition, one of the most effective factors that can affect standing long jump distance and kinematics is the focus of attention used by the athlete. Therefore, the aim of the present study was to compare the effect of internal, external, and holistic focus of attention instructions on standing long jump performance and kinematics. The participants were 30 novices (all males; mean age = 21.70 ± 2.21 years; mean height = 175.73 ± 6.09 cm; and mean weight = 73.76 ± 11.77 kg) who performed 12 standing long jumps in four focus of attention conditions. Internal focus, external focus, holistic focus, and control conditions were implemented in a counterbalanced order. Jump distance and maximum knee flexion angle before take-off were recorded in all trials. The results showed that in relation to the standing long jump performance, the distance was similar in external and holistic focus conditions, and both were superior to internal or control conditions. There was no difference between control and internal focus of attention conditions. The results related to movement kinematics, however, did not report a difference between the maximum flexion angles before take-off. This study replicates the benefits of external and holistic focus instructions for jump distance, but this difference was not a product of different maximum knee flexion angles. It is suggested that coaches implement external and/or holistic focus cues to maximize athlete performance in jumping tasks.